Fenomena Financial Ditress Sebelum dan Sesudah COVID-19 : (Studi Kasus pada Perusahaan Sektor Hotel, Restoran dan Pariwisata yang Terdaftar di Indeks Saham Syariah Indonesia) - Lusi Amelia Ramadhani; Tartila Devy (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Health problems caused by the COVID-19 pandemic have had a major impact on economic contraction in Indonesia. The policies set by the government to prevent the transmission of the COVID-19 virus have an impact on the financial performance of companies in Indonesia. One of the influential sectors includes the hotel, restaurant and tourism sectors which rely on the number of visitors for company operations. The aim of this research is to analyze the comparison of potential financial distress before and after COVID-19 in hotel, restaurant and tourism sector companies listed on the Indonesian Sharia Stock Index using bankruptcy analysis methods, namely the Grover, Springate and Zmijweski methods.This research uses a comparative quantitative approach, which analyzes the comparison between potential financial distress before and after COVID-19. The sample was selected using a purposive sampling method to obtain a sample of 12 companies from a total population of 35 companies in the hotel, restaurant and tourism sector. Data collection uses the documentation method with secondary data in the form of company financial reports for 2017-2022.The results of research based on analytical methods, namely the Grover, Springate and Zmijweski methods, show that there are differences in the potential for financial distress before and after COVID-19. The difference in potential financial distress is higher after COVID-19. Based on the Grover method, the average G-Score produced is -0.136<-0.02. Based on the Springate method, the resulting average S-Score is -0.017<0.862. Based on the Zmijweski method, the resulting average X-Score is -1.345 <0. So from the resulting average it can be concluded that companies in the hotel, restaurant and tourism sectors experienced differences in the potential for financial distress before and after COVID-19 because all three were below the significance value of each method.